Ring-conversion and functionalization of nitrogen-containing heterocycles - Josephitis, Celena M., author; McNally, Andrew, advisor; Bandar, Jeff, committee member; Chung, Jean, committee member; Reisfeld, Bradley, committee member (Colorado State University. Libraries, 2024)
Pyridines and related azines are ubiquitous in pharmaceuticals and agrochemicals development. Chemist rely on the development of new synthetic methods to modify these heterocycles. Described herein are the development of methods to functionalize azines and convert pyridines and diazines into new heterocycles. Novel hydrogenation and molecular editing strategies were designed and leveraged to accomplish this goal. Chapter one introduces the importance of pyridines and related heterocycles in pharmaceuticals as well as methods to access and functionalize these molecules. Both classical and contemporary methods for functionalization and hydrogenation of pyridines are discussed to provide context for this work. Chapter two describes a novel method to selectively reduce pyridines to dihydropyridines, tetrahydropyridines, and piperidines. This method offers a complementary alternative to current hydrogenation or reduction methods, in which the degree of saturation cannot be controlled, and applies to complex azine starting materials. Chapter three explains the importance of structure-activity relationship (SAR) studies and its implications on the drug-discovery process. It also describes classical and contemporary strategies that apply to SAR diversification including de novo heterocycle synthesis and molecular editing strategies. Finally, chapter four presents a novel method for SAR diversification of pyrimidine containing molecules using a deconstruction/reconstruction approach.
Zip file contains supplemental Appendix One and Two.